Casi un bolero - Martin, Ricky; Sony Music Entertainment (Mexico : Sony Music Entertainment, 1998)
Contains the Spanglish version of the single.
Casi Un Bolero (Spanglish version).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English